Penyuluhan Kesehatan pada Pendaki Gunung di Kota Malang - Zaelani, Muhammad Azis; Triyuliarto, Dwiwardoyo; Azis Zaelani, Muhammad; Kinanda, Erka Wahyu; Muthohari, Thoriq Murtadho; Tejamukti L, Arie (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: Mountain climbers are at risk of altitude-related medical problems such as hypothermia, acute mountain sickness (AMS), and traumatic injuries. Adequate knowledge and attitudes are essential to improve preparedness among outdoor enthusiast communities. This community service activity aimed to improve mountaineers’ knowledge and attitudes regarding the prevention, early recognition, and basic management of mountain-related health emergencies through a structured health education program in Malang City. Methods: This community service activity was conducted on August 30, 2025, in Malang City in collaboration with the Tiket Pendakian community. A total of 45 participants took part in health education sessions, interactive discussions, and field simulations on mountain-related health risks and emergency preparedness. Evaluation was carried out through pre- and post-activity assessments of participants’ knowledge and attitudes, as well as feedback on the implementation and benefits of the program. Results: The mean knowledge score significantly increased from 81.9 to 91.6 (+9.6 points; p=0.001; Cohen’s d=0.52), indicating a moderate effect size. The mean attitude score was 34.2 (SD ±3.0) out of a maximum of 40, reflecting a generally positive attitude towards prevention and first aid in outdoor settings. Conclusion: The integrated educational program effectively improved participants’ knowledge of altitude-related hazards and reinforced positive attitudes towards preparedness. Similar interventions could be replicated in other outdoor enthusiast communities to strengthen resilience and self-reliance among climbers.